Chronic lung disease in common variable immune deficiency (CVID): A pathophysiological role for microbial and non-B cell immune factors. (4th July 2017) - Mooney, Denver; Edgar, David; Einarsson, Gisli; Downey, Damian; Elborn, Stuart; Tunney, Michael
Abstract: One of the most common and most severe forms of primary antibody deficiency encountered in the clinical setting is a heterogeneous group of syndromes termed common variable immune deficiency (CVID). This disorder is characterized by reduced immunoglobulin production and increased susceptibility to infection, particularly of the respiratory tract. Infection and subsequent immunological/inflammatory processes may contribute to the development of pulmonary complications such as bronchiectasis and interstitial lung disease. Immunoglobulin replacement and/or antibiotic therapy, to prevent infection, are routinely prescribed treatments. However, chronic lung disease, the major cause of morbidity and mortality in this patient cohort, may still progress. This clinical progression suggests that pathogens recalcitrant to currently prescribed treatments and other immunological defects may be contributing to the development of pulmonary disease. This review describes the potential role of microbiological and non-B cell immunological factors, including T-cells, neutrophils, complement, toll like receptors, and antimicrobial peptides, in the pathogenicity of chronic lung disease in patients with CVID.